23. SURVEY ON THE ABILITY TO PREDICTION OF FALLS IN ELDERLY PATIENTS RECEIVING OUTPATIENT TREATMENT AT HO CHI MINH CITY HOSPITAL FOR REHABILITATION - OCCUPATIONAL DISEASE (Vietnam Journal of Community Medicine, 2025)
Objectives: The study aims to determine the rate and risk of falls, evaluate the role of time-frequency variation, SpO2 and the table in predicting falls in elderly patients.Subject and methods: Descriptive cross-sectional study from April 2023 to June 2024. The study collected convenience 244 outpatients aged 60 years or older who met the sampling criteria and did not meet the exclusion criteria at Ho Chi Minh city Hospital for Rehabilitation - Occupational Disease. During the first visit, patients were examined and assessed for fall risk using the CDC/STEADI 12 independent living questionnaire, and the time-frequency variation index was measured using the Kyto HRM 2511B machine. Falling status will be recorded during the next exploration.Results: The results showed that the 12-question CDC/STEADI questionnaire had a statistically significant predictive ability for falls (p < 0.01). There were statistically significant differences between diastolic blood pressure, BMI, heart rate, and heart rate variability in the fall and non-fall groups. There was no statistically significant difference between SpO2 in fall patients and non-fall patients.Conclusion: Patients at high risk have a greater risk of falling than those at low risk. Diastolic blood pressure, BMI, and heart rate variability can predict the risk of falling. SpO2 has no role in assessing the risk of falling. The use of these parameters can help physicians intervene promptly to reduce the risk of falling.
Keywords: Heart rate variability; fall risk; elderly patients; CDC/STEADI 12-question tool